USING AUTHENTIC MATERIALS IN IMPROVING LISTENING COMPREHENSION SKILL - Nur Syariatin (English Education Study Program, 2020)
The main issue of this study is to describe and identify the students’ low abilities in the Listening Comprehension skill. Authentic materials used in this research are adopted to the syllabus for the students of class ten of senior high school. These materials are in narrative, descriptive and news items. This study used CAR (classroom action research) design by using both qualitative and quantitative approaches. The total numbers of the subject were 38 students. There were only one cycle in this study, the cycle consisted of four activities, namely (1) planning, (2) implementation of the action, (3) observation and (4) reflection. The data collected in this study were derived from observation, questionnaires and field notes. The quantitative data were obtained from the test through post test at the end of the cycle. The results showed that the classical achievement of the students 78.94% and had exceeded the criteria of success which was 75%. The purpose of this study is to help English teachers and students improve the knowledge of the listening comprehension skills.